PENINGKATAN HASIL BELAJAR AQIDAH AKHLAQ MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE - Rosadi, Adi; Lisnawati, Santi (Universitas Islam Negeri Alauddin Makassar, 2020)
Akidah akhlak is one of the main subject on Islamic studies in formal education at Madrasalah schools, both madrasah ibtidaiyah to madrasah Aliyah and in Universiy. This study aims: (1) to determine the application of the Scramble method in the process of learning Akidah Akhlak at Mts Al- Muhajirin Tanah Sareal Bogor and (2) to determine the increase in learning outcomes using the scramble method in Aqidah akhlak lessons for class VIII B students at Mts Al-Muhajirin Tanah Sareal Bogor. The method used in this research is Classroom Action Research(CAR). CAR is implemented as an effort to solve problems that arise in the classroom. This method is carried out through four stages, namely planning, implementing, observing, and reflecting. The number of cycles used in this study were two cycles. The four stages are cycles that are always repeated and carried out using the same steps and are focused on learning akidah akhlak through the application of scramble type cooperative learning model. The results showed that the learning outcomes of students' moral values through the scramble type cooperative learning model had increased. This increase was seen based on the percentage of completeness, namely in cycle I was 56% and cycle II was 84%.